Sleep Disturbances and the Risk of Incident Suicidality: A Systematic Review and Meta-Analysis of Cohort Studies. Issue 7 (19th September 2021) - Dong, Min; Lu, Li; Sha, Sha; Zhang, Ling; Zhang, Qinge; Ungvari, Gabor S.; Balbuena, Lloyd; Xiang, Yu-Tao
ABSTRACT: Objective: The association between sleep disturbances and suicidality is not well understood partly because of the variability in research results. This meta-analysis aimed to investigate the predictive value of sleep disturbances for incident suicidality. Methods: A systematic search was conducted in PubMed, EMBASE, PsycINFO, and Web of Science databases for studies examining sleep disturbances and incident suicidality. Cohort studies were screened following a registered protocol, and the eligible ones were meta-analyzed. Results: Seven studies comprising 1, 570, 181 individuals at baseline, with 1407 attempting suicide and 1023 completing suicide during follow-up, were included. Individuals with baseline sleep disturbances had a significantly higher incidence of suicidality than did those without (relative risk = 2.17, 95% confidence interval [CI] = 1.45–3.24, I 2 = 82.50%, p < .001). The risk of an incident suicide attempt was 3.54-fold higher (95% CI = 3.07–4.09, I 2 = 0%, p = .44), whereas the risk of incident completed suicide was 1.80-fold higher (95% CI = 1.32–2.44, I 2 = 59.33%, p = .01) in individuals with baseline sleep disturbances. Conclusions: Incident suicide attempts and deaths are higher among people with sleep disturbances. Regular screening and preventive measures should be undertaken for people with sleep disturbances to prevent progression into suicide attempts and deaths. Clinical Trial Registration: CRD42019136397 .